Effect of a Gamified Family-Based Exercise Intervention on Adherence to 24-Hour Movement Behavior Recommendations in Preschool Children: Single-Center Pragmatic Trial - Gaizka Legarra-Gorgoñon; Yesenia García-Alonso; Robinson Ramírez-Vélez; Loreto Alonso-Martínez; Mikel Izquierdo; Alicia M Alonso-Martínez (JMIR Serious Games)
Abstract BackgroundAdherence to 24-hour movement behavior recommendations, including physical activity (PA), sedentary time, and sleep, is essential for the healthy development of preschool children. Gamified family-based interventions have shown the potential to improve adherence to these guidelines, but evidence of their effectiveness among children is limited. ObjectiveThis study aimed to evaluate the effectiveness of a gamified family-based exercise intervention in promoting adherence to 24-hour movement behavior recommendations among preschool-aged children. MethodsThis 12-week study is a single-center, pragmatic randomized controlled trial that included 80 preschool children (56% boys) and their families, who were randomly assigned to either the gamification group (n=40) or the control group (n=40). The “3, 2, 1 Move on Study” incorporates family-oriented physical activities and gamification techniques to increase PA domains, reduce sedentary behavior, and improve sleep patterns. The primary outcome was to increase moderate to vigorous PA (MVPA) by 5 minutes/day, as measured by accelerometer at follow-up. Accelerometer-determined daily time spent (PA domains, sedentary behavior, and sleep), physical fitness (cardiorespiratory, speed-agility, muscular, physical fitness z-score), basic motor competencies (self-movement and object movement), and executive function (memory, cognitive flexibility, and inhibitory control) were also included as secondary outcomes. ResultsThe 71 participants included in the per-protocol analyses (32 girls, 45%; 39 boys, 55%) had a mean (SD) age of 5.0 (0.5) years. Change in MVPA per day after the intervention (12 weeks) increased in both groups by +25.3 (SD 24.6) minutes/day in the gamification group and +10.0 (SD 31.4) minutes/day in the routine care group, but no significant between-group differences were observed (8.62, 95% CI –5.72 to 22.95 minutes/day, ηp2Pηp2Pηp2PP ConclusionsIn the “3, 2, 1 Move on Study,” a gamified intervention showed a modest but relevant increase in MVPA and other domains of 24-hour movement behavior among preschool-aged children. Therefore, gamified family-based interventions may provide a viable alternative to improve adherence to 24-hour movement behavior recommendations.